Carbon fiber reinforced ultra-high temperature ceramic matrix composites: A review. Issue 12 (15th August 2019) - Arai, Yutaro; Inoue, Ryo; Goto, Ken; Kogo, Yasuo
Abstract: Recent studies on carbon fiber-reinforced ultra-high temperature ceramic matrix (C/UHTC) composites fabricated by hot-pressing, chemical vapor infiltration, polymer impregnation and pyrolysis, and melt infiltration (MI) are reviewed. Various efforts have been made to improve these preparation processes and to combine two or more of these because they have both the advantages and disadvantages in terms of the processing time, operating temperature, and the porosity of the resulting C/UHTC composites. In addition, the parameters governing the fracture toughness, thermal conductivity, and recession behavior (in oxidizing environments) of these composites have been discussed. This review demonstrates that C/UHTC composites with Zr- or Hf-based UHTC matrices fabricated via MI are potential candidates for advanced heat-resistant structural materials. Highlights: Improvements in the fabrication methods for C/UHTCs are summarized. Zr- or Hf-based UHTCs are effective matrices for C/UHTCs. Weak fiber/matrix interface is required to increase the toughness of C/UHTCs. Thermal conductivity of C/UHTCs strongly depends on their fiber architecture.